Paying Mr. Bewick: Review of Diana Donald, The Art of Thomas Bewick - Irmscher, Christoph (Humanimalia, 2015)
Diana Donald, The Art of Thomas Bewick (with contributions by Paul F. Donald). London: Reaktion Books, 2013. 328 pp. + 60 color plates, 150 halftones. £40.00; 65.00.